PERANCANGAN SISTEM INFORMASI PEMINJAMAN RUANG LABORATORIUM KOMPUTER BERBASIS WEBSITE PADA LSI UMY - Wahid Budi Nugroho; Riyan Latifahul Hasanah (Jurnal Komputer dan Teknologi, 2025)
The Information Systems Institute (LSI) at the University of Muhammadiyah Yogyakarta (UMY) is a work unit responsible for managing technology and IT systems. LSI UMY faces several challenges in its operations, such as the process of borrowing computer laboratory space still using conventional methods. The high demand has increased the workload which makes it difficult for LSI staff to manage the request. This project uses the Agile method. Its development goes through several stages, namely planning, implementation, testing, documentation, deployment, and maintenance. The purpose of this study is to build a web-based computer laboratory space borrowing information system to overcome problems in the borrowing process, produce better and more organized reports, make it easier for borrowers, provide more accurate information and optimal evaluation of the existing system. Website testing uses Web Application Testing 6.0 (WAPT) to ensure optimal performance and Zed Attack Proxy (ZAP) to validate website security. With the application of a web-based room borrowing system at LSI UMY, it can simplify the borrowing process, provide accurate and relevant data, and make reports more structured and efficient for staff.